Diversity of rhizospheric fungi from Nanhaia speciosa and their capacity to degrade insoluble phosphate and organic manners - PHONG XUAN ONG; THIEP VAN NGUYEN; LIEN THUY BUI; NGUYEN THI MINH NGUYET; KHANG TAN DO; GIA HUY TRAN; PHI BANG CAO; HA DUC CHU; NGOC BICH PHAM; THACH VAN PHAN; HONG VIET LA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ong PX, Nguyen TV, Bui LT, Nguyet NTM, Do KT, Tran GH, Cao PB, Chu HD, Pham NB, Phan TV, La HV. 2024. Diversity of rhizospheric fungi from Nanhaia speciosa and their capacity to degrade insoluble phosphate and organic manners. Biodiversitas 25: 3585-3595. The rhizosphere is the microenvironment for interactions between plant roots and surrounding microbes. Rhizospheric fungi play a vital role in plant growth through various mechanisms. The aim of this study was to isolate and identify the fungi from the soil around the root of Nanhaia speciosa (Champ. ex Benth.) J.Compton and Schrire and to test their ability to degrade insoluble phosphate, cellulose, and xylan. The result showed that a total 72 fungal species were isolated from the soil of the rhizosphere of N. speciosa. These isolates belonged to six genera, namely Penicillium, Trichoderma, Aspergillus, Talaromyces, Purpureocillium, and Chaetomium. Results showed that 50% of the isolated strains belonged to the genus Penicillium. Moreover, it was also recorded that out of 10 fungal strains, only five fungal strains produced the phosphate decomposition enzyme (+), with the Tv-LHOP3 (Trichoderma virens LHOP3) and Tk-LHOP1 (Trichoderma koningiopsis LHOP1) strains expressed the highest phosphate solubility with the PSI of two strains were 2.22 and 2.18, respectively. All strains exhibited cellulose ability, Pj-LHOP2 (Penicillium janthinellum LHOP2) showed the highest degradation ability with a halo diameter of 7.52 cm, followed by strain Tk-LVHOP1 (Trichoderma koningiopsis LHOP1) with a diameter of 7.38 cm. The xylan degradation ability test demonstrated that the strain Tv-LHOP2 (Trichoderma virens LHOP2) had the highest halo diameter of 8.87 cm, followed by Tk-LHOP1 (Trichoderma koningiopsis LHOP1) had 8.80 cm and Tv-LHOP3 (Trichoderma virens LHOP3) had halo diameter of 8.63 cm. These findings suggest the potential of these fungal strains as biofertilizers to enhance nutrient availability and promote sustainable agricultural practices, particularly in improving the growth and yield of medicinal plants like Nanhaia speciosa.